Spa Typing of Staphylococcus aureus in a Neonatal Intensive Care Unit During Routine Surveillance. (15th June 2021) - Grohs, Emily; Hill-Ricciuti, Alexandra; Kelly, Nicole; Messina, Maria; Green, Daniel A; Geng, Wenjing; Annavajhala, Medini K; Zachariah, Philip; Mathema, Barun; Uhlemann, Anne-Catrin; Saiman, Lisa
Abstract: Background: Staphylococcus aureus protein A ( spa ) typing can be used to expand characterization of the epidemiology of methicillin-susceptible S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA) in neonatal intensive care units (NICU). Methods: From January 2017 to June 2018, twice-monthly surveillance for S. aureus was performed in an academically affiliated NICU. Decolonization of infants colonized with S. aureus included chlorhexidine gluconate bathing and/or mupirocin for those with mupirocin-susceptible strains. Spa typing and mupirocin-resistance testing were performed. Demographic and clinical characteristics were compared between infants colonized with MSSA vs MRSA and infants with and without the most common MSSA spa type, MSSA-t279. Results: Overall, 14% and 2% of 1556 hospitalized infants had positive surveillance cultures for MSSA and MRSA, respectively. Thirty-six infants harbored unique MSSA spa types, 5 infants harbored unique MRSA spa types, and 30 MSSA and 6 MRSA spa types were identified in ≥2 infants. No outbreaks were identified during the study period. MSSA-t279 was isolated from 3% of infants and largely detected from infants hospitalized in one section of the NICU; 96% of t279 isolates were mupirocin resistant. Infection rates, length of hospitalization, and mortality were similar among infants initially colonized with t279 vs other MSSA spa types. Conclusions: The MSSA colonization burden was 5-fold larger than that of MRSA. Numerous unique spa types were identified. The most common spa type, MSSA-t279, was not associated with increased morbidity or mortality but was mupirocin resistant and associated with clustered NICU beds. This suggests potential transmission from the environment, shared staff, and/or workflow issues requiring further study. Other decolonization strategies for S. aureus in the NICU are needed. Abstract : Methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA) colonized 14% and 2% of 1556 infants, respectively; 30/61 MSSA and 6/11 MRSA spa types were shared by ≥2 infants. While MRSA is prioritized for prevention, prevention efforts for MSSA also should be prioritized due to greater burden.